Morphometric Study of Nile Tilapia (Oreochromis niloticus) in Grow-Out Ponds at the Freshwater Aquaculture Center (PBIAT) Polnustar - Indriani, Yeni; Mose, Numisye Iske; Manganang, Yessi Ayu Putri; Ulaan, Magdalin; Saselah, Jetti Treslah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Nile tilapia (Oreochromis niloticus) is an important freshwater aquaculture species whose morphometric characteristics provide essential insights into growth performance and sexual dimorphism in cultured populations. This study aimed to analyze the morphometric traits of male and female Nile tilapia reared in grow-out ponds at the Freshwater Aquaculture Center (PBIAT) of Politeknik Negeri Nusa Utara. Thirty fish were sampled using simple random sampling, and eleven morphometric parameters were measured alongside water quality observations to evaluate the suitability of the rearing environment. The results showed significant differences in several morphometric traits, including total length, standard length, body length, head length, body height, snout length, and caudal peduncle height, all of which were higher in males, with average body weight also greater in males (257.75 g) than females (205.15 g). Water quality parameters remained within optimal ranges for tilapia culture throughout the study period. The study concludes that male tilapia exhibit superior morphometric performance compared to females, indicating their potential advantages for selective breeding and improved grow-out production, and recommends further research involving larger populations and genetic evaluation to strengthen the use of morphometric indicators in tilapia aquaculture.